Conductance of Sodium dodecyl sulphate in Presence and in Absence of KCl and NaBr in Methanol-Water mixed solvent media at 308. 15 K - Niraula, Tulasi Prasad; Chatterjee, Sujeet Kumar; Bhattarai, Ajaya (Journal of Nepal Chemical Society, 2013)
Correction: On 10/01/2014, the first author of this paper was changed from Tulsi Ram Niraula to Tulasi Prasad Niraula Precise measurements on conductivity of sodium dodecyl sulphate in presence and in absence of KCl and NaBr in methanol-water mixed solvent media containing 0.1, 0.2, 0.3, and 0.4 volume fractions of methanol at 308.15K are reported. The concentrations were varied from ~ 0.001 to ~ 0.05 mol-1. The results showed a sharp increase in conductivity with increase in concentration of sodium dodecyl sulphate. Also,the conductivity of sodium dodecyl sulphate increases with addition of salts. The conductivity of sodium dodecyl sulphate decreases with increase in amount of methanol. The conductance of sodium dodecyl sulphate is found more in presence of KCl than NaBr in methanol-water mixed solvent media containing 0.1, 0.2, 0.3, and 0.4 volume fractions of methanol. DOI: http://dx.doi.org/10.3126/jncs.v29i0.9230 Journal of Nepal Chemical Society Vol. 29, 2012 Page: 5-10 Uploaded date : 12/3/2013